Bridging the Gap Between AI and Reality: Second International Conference, AISoLA 2024, Crete, Greece, October 30 – November 3, 2024, Selected Papers (Lecture Notes in Computer Science; Computer Science; Computer Science (R0), 2026)
This open access book constitutes revised selected papers from the Second International Conference on Bridging the Gap between AI and Reality, AISoLA 2024, which took place in Crete, Greece, in October/November 2024. The papers included in this book extend the presentation in the AISoLA 2024 on-site proceedings. They focus on the following topics: AI-Assisted Programming; health care approaches using formal methods and AI; responsible and trusted AI: an interdisciplinary perspective; statistical model checking; and verification for neur-symbolic artificial intelligence.